2018
DOI: 10.33885/sf.2017.46.1177
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus djamor, un hongo con potencial aplicación biotecnológica para el neotrópico

Abstract: Antecedentes: Pleurotus djamor es un hongo pantropical, cultivado comercialmente en algunos países asiáticos. Debido a sus características de crecimiento, ciclos de cultivo cortos y aceptable valor nutrimental, es una especie comestible adecuada para su propagación y consumo en las regiones cálidas del mundo.Objetivo: El propósito de la presente revisión fue conocer los avances en la biología y cultivo de esta especie, con la finalidad de incrementar su potencial aprovechamiento en el neotrópico.Método: Se hiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
2
12
0
3
Order By: Relevance
“…In this study the CP content of the fruiting bodies in our WP and WG treatments was found to be within the ranges established for the genus Pleurotus; that is, 17-25% (Lelley 2017), with 20.3% of CP for P. ostreatus (Del Toro et al 2018), and 20.7-28% for P. djamor (Salmones 2017).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In this study the CP content of the fruiting bodies in our WP and WG treatments was found to be within the ranges established for the genus Pleurotus; that is, 17-25% (Lelley 2017), with 20.3% of CP for P. ostreatus (Del Toro et al 2018), and 20.7-28% for P. djamor (Salmones 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Some 50 species of this genus have been reported. Its cultivation requirements and nutraceutical and biodegradative properties have attracted interest, and it is now a promising agroindustrial product with expanding cultivation in Latin America and other areas of the world (Royse and Sánchez 2001;Barba et al 2016;Salmones 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fonte: Autores. Dados da literatura demonstram que o gênero Pleurotus demonstra grande preferência por resíduos lignocelulósicos, substratos ricos em celulose, hemicelulose e lignina que estimulam a síntese de enzimas degradadoras essenciais para o crescimento dos cogumelos (Salmones, 2018;Singh & Singh, 2018). Assim como as demais espécies do gênero, Pleurotus djamor também apresenta a habilidade para degradar lignina e polímeros presentes na parede celular vegetal, capacidade comprovada ao utilizar fibra de coco (Theradinami, Thangeshwari, Arulsamy, & Parthasarathy, 2019).…”
Section: Resultsunclassified
“…Resíduos agroindustriais influenciam significativamente no crescimento, na qualidade do micélio e na formação de basidiomas. A estrutura, a composição desses substratos e a relação carbono/nitrogênio provavelmente fornecem condições físicas e nutricionais, parâmetros favoráveis para o desenvolvimento do micélio e reprodução das diversas espécies de cogumelos (Salmones, 2018;Osunde, Olayinka, Fashina, & Torimiro, 2019;Toan & Qui, 2018;Wu et al, 2019).…”
Section: Resultsunclassified